Actual evapotranspiration of the orange orchard in northern Sinai, Egypt - Jerzy Jan Niziński; Agnieszka Ziernicka-Wojtaszek; Leszek Książek; Krzysztof Gawroński; Jean-Pierre Montoroi; Alaa Zaghloul; Rafat R. Ali; Mohamed Saber (Acta Scientiarum Polonorum. Formatio Circumiectus)
Studies on soil-water management in the Nile Delta and Northern Sinai (Egypt) were carried out in 2011–2013 by the Institut de Recherche pour le Développement. The El-Salam orange orchard was selected as a ‘standard’ station to study the management of appropriate irrigation, including the development of a model to assist in the management of irrigation of other crop covers in the Nile Delta. The model simulated actual evapotranspiration with a one-day step resolution, using the approach of Penman-Monteith (with daily input data, i.e. standard data from the national network of weather stations), by taking account of the specificity of the crop cover (cover resistance). We compared the amounts of irrigation applied to the orange orchard (Imean = 994.3 mm • year–1; 2.7 mm • day–1; crop coefficient Ea/ET0 = 0.78) with the requirements of water estimated by the model (Easimulated). This comparison enabled us to propose a daily amount required for irrigation. It is reasonable to sustain water losses of 94,570 m3 water • year–1 for the total area of the plantation (80 ha; drainage from the root zone), that is, 1,182 m3 water • year–1 • ha–1. These water losses involve hydraulic adjustment of the sites of crop production and the costs of routing water.